Insurance as an Instrument Hedging of Exclusion of Young Mothers from the Labour Market - Machowiak, Mira (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The paper analysis the situation of woman who are going back on the labor market after period of pregnancy and babysitting. After time of taking care of baby woman position on labor market is quite poor and in most cases worst than before babysitting. Business practice shows that time when woman if not working because of delivering a child or babysitting has many negative effects on her future employment status. In the article were also discussed current trends in Polish system that secure labor position for young mothers. Unfortunately system is not good enough, it does not solve problem and needs some new solutions. Article presents innovative form of preventing this negative effects. The proposed solution is to create special insurance for woman who are planning to get pregnant and who are predicts that it can effects negative on their future labor position.